(untitled) (International Journal of Built Environment and Sustainability, 2021)
Industrial Site selection is one of the rudimentary decisions to expand or relocate any business start-up process. This paper aimed at finding suitable location for possible industrial site as per reaching the SDGs taking Khulna City as a case. For instance, the targeted SDGs Goal 9: Resilient Infrastructure, Sustainable Industrialization and Innovation. The research also focused on the existing locations of the industries in the Khulna city and filled the gap to propose the new locations. To achieve this, a three-stage method have been adopted. At first, the existing industries were categorized on the basis of basic/non-basic, small/large scale, input/output characteristics in geo-spatial environment. Location Quotient (LQ) technique was applied to detect basic, non-basic industries and industrial zone. Then, Analytic Hierarchy Process (AHP) was conducted to define weights of important criterion such as temperature, slope, water body, land use, city center, connectivity and structures. The calculation of Consistency Ratio (CR<0.1) showed rational consistency of the factors. Finally, Multi Criteria Decision Analysis (MCDA) was adopted in GIS platform to address the suitable locations. The analysis shows 10% of the total KCC area is suitable for constructing industrial zones. According to the results most of the suitable land was found in the eastern side and a few suitable lands was found in the upper western part of the map. Another findings state that, 5% change in vacant land can increase this percentage to 17% which eventually escalates sustainability, resilience and locational advantages. In addition, the study assesses the land use change in Khulna City Corporation for recent years which have potential for industrial establishment through land suitability analysis (LSA) to emphasize both land use and industries with sustainable development